2017
DOI: 10.9790/5933-0804011632
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Monetary Policy (Interest Rate) Regimes on the Performance of the Banking Sector in Nigeria

Abstract: This paper examined the impact of monetary policy regimes on the performance of ommercial banks in Nigeria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
3
2
0
Order By: Relevance
“…The results indicate that Monetary Policy has a significant negative impact on return on investment; therefore, an increase in monetary policy will likely decrease mutual fund performance. This is in line with the study conducted by Ndubuaku et al (2017) who established that monetary policy has a significant negative relationship with banking performance in Nigeria. The result is also consistent with the study done by Adam et al (2014) who brought to the fore that monetary policy negatively affects Banking financial performance in Pakistan.…”
Section: Panel Ardl Results For Macroeconomic Determinants Of Mutual Fund Performancesupporting
confidence: 92%
See 1 more Smart Citation
“…The results indicate that Monetary Policy has a significant negative impact on return on investment; therefore, an increase in monetary policy will likely decrease mutual fund performance. This is in line with the study conducted by Ndubuaku et al (2017) who established that monetary policy has a significant negative relationship with banking performance in Nigeria. The result is also consistent with the study done by Adam et al (2014) who brought to the fore that monetary policy negatively affects Banking financial performance in Pakistan.…”
Section: Panel Ardl Results For Macroeconomic Determinants Of Mutual Fund Performancesupporting
confidence: 92%
“…The short-run effect of the T-Bill is consistent with the findings in Marfo (2016) and Mwangi, 2013) but opposed to the outcomes in Ongeri (2014) and Kariuki (2014). The long-run effect of the T-Bill is, however, in harmony with Kariuki (2014) and Ongeri (2014) but opposed to Mwangi (2013) and Marfo (2016). Theoretically, the T-Bill rate and Monetary Policy Rate have a positive relationship as the two serve as signaling or leading indicators from an economic policy perspective.…”
Section: Panel Ardl Results For Macroeconomic Determinants Of Mutual Fund Performancesupporting
confidence: 84%
“…Empirically, the findings of the study confirm the findings of Udeh (2015) that cash reserve ratio, liquidity ratio and interest rate did not have a significant impact on the profit before tax of Zenith Bank Plc but the minimum rediscount rate was found to have a significant effect on the profit before tax of the bank. It also validates the findings of Ndubuaku et al (2017) who found that monetary policy rate during the post SAP period had significant impact on the total assets value, deposit mobilization, loans and advances and credit to the private sector respectively. Okpara (2009) revealed that the dependent variables were responsible for half of the variations in the returns on assets and the findings of…”
Section: Regression Coefficient and T-statisticssupporting
confidence: 88%
“…However, the minimum rediscount rate was found to have a significant effect on the profit before tax of the bank. Ndubuaku et al (2017) examined the impact of monetary policy regimes on the performance of commercial banks in Nigeria. The paper used Descriptive and Ex-post Facto Research Design.…”
Section: Investment and National Incomementioning
confidence: 99%
“…This study takes its source from the linear specifications of Ubi, Lionel and Eyo (2012), Udeh, (2015) Onodugo et al, (2016) and Ndubuaku et al, (2017) However, these specifications are replicated using different variables as stated in my baseline equations as follow. The ARDL form can be given as:…”
Section: Model Specificationmentioning
confidence: 99%